Improvement Strategy of Principal’s Managerial Performance through Adaptability and Organizational Commitment - Tri Satyawati, S; EkoSiswoyo, R (KnE Social Sciences, 2018)
The duty and role of the principal as a manager in the education unit determines the quality of work. Base on the facts through the environment in elementary school Semarang Regency shows that not all of the principals have managerialcompetence in the high level. The purpose of this research is to reveal the effect of adaptability, and organizational commitment toward improvement of the principal’s managerial performance. The method used in this research is quantitative methods. The samples in this research are determined baseon Cluster Sampling technique totally 127 people. The data are collected through questionnaires that have been tested relates to the validity and reliability. The technique of analyzing data usespath analysis with software call SPSS 21. The results show that the improvement of managerial performance of elementary school principals in Semarang Regency is influenced by the adaptability and organizational commitment. Suggestion from the results of this research is for the principals to implement the strategy of proactive attitude internally and externally to mental changes in the school and strengthen organizational commitment to improve managerial performance. Department of Education, Culture, Youth and Sports in Semarang Regency needs in accordance with plan and periodically to conduct education and training of principal’s managerial competence and to optimize the role of supervisor in constructing and assisting the principal of the target school.